Influence of Filler from a Renewable Resource and Silane Coupling Agent on the Properties of Epoxidized Natural Rubber Vulcanizates - Wiphawadee Pongdong; Charoen Nakason; Claudia Kummerlöwe; Norbert Vennemann (Journal of Chemistry)
Rice husk ash (RHA) was used as a reinforcing filler in epoxidized natural rubber (ENR) with various loading levels (0, 10, 20, and 30 phr), and silica filled ENR was also studied for comparison. The effects of RHA content on cure characteristics, mechanical properties, dynamic mechanical properties, and thermoelastic behavior of the filled ENR composites were investigated. It was found that the incorporation of RHA significantly affected the cure characteristics and mechanical properties. That is, the incorporation of RHA caused faster curing reactions and increased Young’s modulus and tensile strength relative to the unfilled compound. This might be attributed to the metal oxide impurities in RHA that enhance the crosslinking reactions, thus increasing the crosslink density. Further improvements in the curing behavior and the mechanical properties of the filled composites were achieved by in situ silanization with bis(triethoxysilylpropyl) tetrasulfide (Si69). It was found that the rubber-filler interactions reinforced the composites. This was indicated by the decreased damping characteristic (tan ⁡δ) and the other changes in the mechanical properties. Furthermore, the ENR composites with Si69 had improved filler dispersion. Temperature scanning stress relaxation (TSSR) results suggest that the metal oxide impurities in RHA promote degradation of the polymer network at elevated temperatures.